2004
DOI: 10.1097/01.alc.0000108658.00243.bf
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Ethanol Consumption Reduces δ‐and μ‐Opioid Receptor–Stimulated G‐Protein Coupling in Rat Brain

Abstract: DPDPE significantly stimulated [35S]-GTPgammaS binding in the hippocampal dentate gyrus (DG), CA1, cerebellum, and inferior colliculus of untreated pair-fed controls. By contrast, DPDPE-stimulated [35S]-GTPgammaS binding was reduced significantly in those brain regions in the ethanol-consuming group. DAMGO stimulated [35S]-GTPgammaS binding in cortex, caudate, nucleus accumbens, DG, CA1, and superior and inferior colliculi, whereas the DG, CA1, and colliculi showed a significant reduction of binding after chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 36 publications
4
25
0
1
Order By: Relevance
“…In this study, ethanol exposure significantly reduced l-opioid functional activity in the CPu, AccC, and AccS. The reduction in l-opioid-stimulated [ 35 S]GTPc binding in the brain regions closely involved in reward responses after prolonged ethanol exposure is consistent with previous findings (Chen and Lawrence, 2000;Oliva and Manzanares, 2007;Saland et al, 2004;Sim-Selley et al, 2002). Treatment with AM251 fully blocked the effects of voluntary ethanol consumption on l-opioid receptors in the brain regions examined.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, ethanol exposure significantly reduced l-opioid functional activity in the CPu, AccC, and AccS. The reduction in l-opioid-stimulated [ 35 S]GTPc binding in the brain regions closely involved in reward responses after prolonged ethanol exposure is consistent with previous findings (Chen and Lawrence, 2000;Oliva and Manzanares, 2007;Saland et al, 2004;Sim-Selley et al, 2002). Treatment with AM251 fully blocked the effects of voluntary ethanol consumption on l-opioid receptors in the brain regions examined.…”
Section: Discussionsupporting
confidence: 92%
“…The developmental decrease in TAN67-mediated analgesia is comparable to age-related reductions in spinally administered DPDPE-mediated analgesia (Crisp et al, 1994a,b;Rahman and Dickenson, 1999). Although binding studies revealed no age-related changes in receptor density or affinity in the spinal cord (Hoskins et al, 1998;Rahman et al, 1998), our studies show a developmental decrease in DOP-R activity in the dorsal striatum using the [ (Cichewicz et al, 2004;Narita et al, 2007), caudate nucleus, and nucleus accumbens (Saland et al, 2004), consistent with our findings of low DOP-R coupling in the dorsal striatum of aged rats.…”
Section: Developmental Decrease In Dop-r Activitysupporting
confidence: 64%
“…Furthermore, we show that intermittent high ethanol consumption, but not continuous ethanol or water consumption, from young adulthood results in an increase in DOP-R activity in the dorsal striatum. Previous studies showed that long-term ethanol-consuming rats have increased striatal DOP-R binding (Lucchi et al, 1984(Lucchi et al, , 1985, although other studies show no changes (Turchan et al, 1999;Saland et al, 2004). This suggests that long-term intermittent high ethanol consumption leads to changes in DOP-R activity.…”
Section: Discussionmentioning
confidence: 90%
“…Chronic ethanol exposure reduces MOPr coupling to G proteins (Chen and Lawrence, 2000;Sim-Selley et al, 2002;Saland et al, 2004). In the whole animal, acute exposure to ethanol reverses morphine tolerance (Hull et al, 2013), whereas chronic exposure to ethanol reduced the antinociceptive effect of morphine and DAMGO (He and Whistler, 2011).…”
Section: Discussionmentioning
confidence: 99%